Scanning Tunneling Microscopy Observation of Sulfur Electrodeposits on Graphite Single Crystals - Zubimendi, J. L. (1996)
The early stages of sulfur deposit growth on highly oriented pyrolytic graphite (HOPG) caused by HS- electrooxidation in a neutral buffered solution have been investigated using electrochemical techniques and ex situ scanning tunneling microscopy (STM). In this system sulfur deposition has been observed at −0.80 V vs SCE, i.e. a potential more negative than the reversible potential for the HS-/S reaction. The charge density was equivalent to an average surface coverage by sulfur atoms θ ≅ 1/3 monolayer (ML). Ex situ atomic resolution STM images of the layer electrodeposited at −0.8 V show sulfur submonolayers and large uncovered HOPG domains. Sulfur electroadsorption layers appear as a diluted (√3×√3) surface phase with S atoms atop C atoms of the graphite hexagons and the S−S interatomic distance d(S−S) = 0.42 nm. Further addition of S atoms to a diluted sulfur phase resulted in the formation of sulfur trimers with three S atoms placed atop the three C atoms constituting the graphite hexagons. In this case d(S−S) = 0.24 nm. Neighbor trimers originate a filled hexagonal lattice. Ex situ STM images of overpotential deposited sulfur also show submonolayer sulfur domains with a second hexagonal (√3×√3)R30° sulfur lattice with d(S−S) = 0.42 nm. A further increase of θ produces either a new honeycomb lattice with d(S−S) = 0.24 nm or a rectangular lattice formed by rows of S atoms with d(S−S) = 0.21 nm and row separation d(S−S) = 0.37 nm.